2014
DOI: 10.1177/0954407014537642
|View full text |Cite
|
Sign up to set email alerts
|

Study of the dynamic behaviour of a human driver coupled with a vehicle

Abstract: In this paper a 15-degree-of-freedom human-seat vibratory model is developed using anthropomorphic modelling and the model is coupled with a typical seven-degree-of-freedom small passenger car to study the dynamic response of a human driver due to vehicle vibrations. The coupled model is analysed by MATLAB simulation for the ride dynamic behaviour of the human driver under a harmonic input excitation in the frequency range 0-40 Hz. The ride behaviours in terms of the vertical accelerations of different segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Human body can be treated as various degree of freedom vibration systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . The reason for us to use this simplified 5-DOF vertical human body vibration model is that this model can capture the most important features of human's perception and response to vibration in a human-vehicle system, while the model itself is simple to implement in a remote portable or distributed environment in Industry 4.0 framework.…”
Section: Simplified 5-dof Human Body Vibration Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Human body can be treated as various degree of freedom vibration systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . The reason for us to use this simplified 5-DOF vertical human body vibration model is that this model can capture the most important features of human's perception and response to vibration in a human-vehicle system, while the model itself is simple to implement in a remote portable or distributed environment in Industry 4.0 framework.…”
Section: Simplified 5-dof Human Body Vibration Modelmentioning
confidence: 99%
“…In 2008, E Zhang studied the different vibration parameters of the human body vibration characteristics [15] . Recently, Reddy P S et al proposed a 15-DOF human body model to include the left and right lower and upper arms, as well as neck in the human-vehicle vibration model [16] . Ten subjects were tested in whole body vibration with five frequencies in vertical direction, and a hybrid Polaris spectra system was used to obtain the seat to head transmissibility [17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 15-degree-of-freedom male driver model, which includes 14 body parts, has been developed for vibration evaluation, and its parameters, such as stiffness and damping, have been determined. 12,13 Loutridis et al 14 found that when tractors transit on asphalt roads, drivers traveling at a constant speed were less comfortable than those performing regular pedal operations. By contrast, when transiting rough roads, tractor drivers traveling at a constant speed were more comfortable than those performing regular pedal operations.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have established 15-DOF (degree of freedom) human body model and 7-DOF vehicle model to study the influence of 0-40 Hz vibration frequency on human comfort. 1 Some researchers have established vibration analysis models for pedestrians and vehicles to evaluate driving comfort in different vibration conditions. 2,3 In order to improve the ride comfort of some specially equipped cabs, scholars calculated the natural frequency and vibration characteristics of the whole vehicle through experiments, and reduced the frequency and vibration in their designs.…”
Section: Introductionmentioning
confidence: 99%